PSO-Based Multi-Criteria Economic Dispatch Considering Wind Power Penetration Subject to Dispatcher's Attitude - Lingfeng Wang; Singh, C. (2006 38th Annual North American Power Symposium, 2006)
Significant attention has been paid to the renewable energy resources such as wind power in recent years. It has potential benefits in curbing emissions and reducing the consumption of irreplaceable fuel reserves. However, the penetration of wind power into traditional fuel-based generation systems will also have some implications such as security concerns due to its unpredictable nature. Thus, in economic power dispatch with wind power penetration, a reasonable tradeoff between system risk and operational cost is desired. In this paper, a bi-objective economic dispatch problem considering wind penetration is formulated, which treats economic and security impacts as conflicting objectives. Different fuzzy membership functions are used to reflect the dispatcher's attitude toward the wind power penetration. A modified multi-objective particle swarm optimization (MOPSO) algorithm is adopted to develop a power dispatch scheme which is able to achieve compromise between economic and security requirements. Numerical simulations including sensitivity analysis are reported based on a typical IEEE test power system to show the validity and applicability of the proposed approach.